Lexical semantics and diachronic morphology : the development of -hood, -dom and -ship in the history of English - Trips, Carola (Linguistische Arbeiten (Max Niemeyer Verlag), 2009)
This book is the most comprehensive study to date of the development of the three suffixes -hood, -dom and -ship in the history of English. Based on data from annotated corpora it provides an in depth investigation from Old English to Modern English and shows that structurally the three suffixes developed from syntactic heads (nouns) via morphological heads in compounds to morphological heads in derivations. Being an instance of morphologisation the rise of suffixes clearly shows that word formation is not part of the syntactic module. This development is triggered by semantic change, more pre.